Suicide as a Social Problem among Young People and Adolescents in Aktobe City - Yermukhanova, Lyudmila Sergeevna; Kushimov, Bekhzan Izbergenovich; Zhexenova, Azhar Nikolaevna; Turebaev, Mukhit Nauryzgaliyevych; Salakhova, Nadira Kairatovna; Mukhanbediyarova, Ardak Zhenisbaikyzy (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The purpose of this article is to study the cause-effect relationship leading to suicide based on the results of two questionnaires conducted in Marat Ospanov State Medical University (Aktobe city). Method: The study involves two questionnaire surveys (2016 and 2017 years) of 1,000 1st-4th year students of the West Kazakhstan Marat Ospanov State Medical University based on the Beck Scale for Suicidal Ideation (aimed at determination of the level of depressive state, the portrait of a suicide) and the second similar questionnaire involved 500 respondents of the same University using the Dembo-Rubinstein method in Prikhozhan’s modification, that is aimed at determining the level of self-esteem and aspiration. Results: The questionnaires conducted in Marat Ospanov State Medical University allowed to determine the levels of suicidal behaviour among young people and adolescents of Aktobe city as well as determine the criteria, levels and reasons of suicidal intentions in percentage and by gender criterion. The results are partially presented in the form of diagrams. Conclusions: The study may be used for developing the complex methodologies of suicide prevention among young people and adolescents in Aktobe city and everywhere in the world where such a problem arises sharply. Such a kind of study was firstly conducted with usage of declared methods in Aktobe city.